Analisis Pengaruh Pengembangan Karir dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Bumjin Electronic Indonesia - Rena Nur Aeni; Rakhmat; Nurfai (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
The main factor that can affect employee work productivity is career development. Career development will be very useful for companies to ensure the right employee in a position. Another thing that is an important factor in achieving employee work productivity is how the environment conditions around it. In this study, researchers took the object of PT Bumjin Elektronik Indonesia which is located in the industrial area Jababeka 3 Block A5B, Cikarang - Bekasi. In this study, the authors conducted library and field research (observations, interviews, and questionnaires) with quantitative analysis methods and descriptive analysis using the SPSS version 26 application which included regression coefficient analysis, coefficient of determination analysis, t test, and f test. The results of calculating the multiple linear regression coefficients obtained an equation between career development variables (X1) and work environment (X2) on employee productivity (Y). Y = 9.973 + 0.441 X1 + 0.258 X2. The results of the coefficient of determination show that the productivity variable is influenced by career development and work environment variables of 0.775 or 77.5% and the remaining 23.5% is influenced by other factors or other variables not examined. The results of calculations using the T-test hypothesis test between career development and employee work productivity obtained a Tcount of 3.962 > Ttable of 1.678. So, the conclusion is that H0 is rejected and H1 is accepted. These results indicate that there is an influence between career development (X1) on employee work productivity (Y). The results of the F-test analysis show that the value obtained for Fcount is 41.303 > Ftable 3.20 with a significance value of 0.000 less than a probability of 0.05. This means that H0 is rejected and H3 is accepted, meaning that statistically it shows that the variables Career Development and Work Environment have a significant effect on Employee Productivity at PT. Bumjin Electronics Indonesia.